Desarrollo de una herramienta de modelado en alta resolución para simular la demanda energética y la producción de energía fotovoltaica in situ: Aplicaciones en Costa Rica - Ruiz-Vásquez, Sophia (2019)
Strategies towards more energy-efficient systems imply the integration and application of urbanenergy analysis tools in order to support the sustainable energy systems. Energy systems suchas intermittent solar power, requires research into the comprehensive analysis of the matchingcapability between the demand and the production. In order to perform the energy matchinganalysis, the aim must involve minimal source of error therefore, more accurate results can beobtained.In certain applications of energy simulation, the commonly used time step is one hour,nevertheless studies have shown that this can be a significant source of error. For theidentification of the impact that time-step have in simulations, holistic models in high resolution were created. With the models, using time a time step of 1 minute, more precise and accurateresults could be obtained.The generated PV on-site production model is based on a model developed by the researchgroup Energy Efficient and Smart Cities (EESC). Relevant data needed for the model, such asirradiance and incident global radiation; was obtained using the software Meteonorm. For thehigh-resolution model of domestic electricity demand, the model developed by the Centre forRenewable Energy Systems Technology of Loughborough University, was used and modifiedusing relevant information from Costa Rica.This model implicates PV modules on-site production and adequately represents the domesticelectricity demand. Hence analyses of energy matching capability calculations, such as theon-site energy fraction index (OEF) which asses how much demand can be covered by theon-site energy generation and the on-site energy matching index (OEM) which indicates howmuch on-site generation can be consumed in the system rather than being exported or wasted;showed that the usage of coarser resolutions leads to overestimated this capability, and thesame time the error percentage is bigger.